MP05: Do emergency department staff use a current domestic violence documentation tool or other forms of intimate partner violence documentation in patient records?. (15th May 2017) - Vonkeman, J.; Atkinson, P.R.; Fraser, J.; McCloskey, R.
Abstract : Introduction: Domestic violence (DV) rates in smaller cities been reported to be some of the highest in Canada. It is highly likely that emergency department staff will come across victims of intimate partner violence (IPV) in their daily practice. The purpose of this study is to better understand current practices for detecting IPV as we are currently uncertain whether patients are assessed for IPV and what the current documentation practices are.Methods: A standardized retrospective chart review, following principles outlined by Gilbert et al. 1996, was completed by two researchers to capture domestic violence documentation rates in patients presenting to the ED between January and April 2015 with injuries that may have been caused by IPV. To assess self-reported documentation/questioning practices, a cross-sectional online survey was distributed to ED staff via staff email lists three times between July and October 2016, with a response rate of 45.9% (n=55). The primary outcome was DV field usage. Secondary outcomes included documentation in patient charts and current questioning habits.Results: Overall, we found documentation in 4.64% of all included patient charts (n=366). No documentation was noted in the DV field. 52.4% patients with deliberate injuries had no documentation of assailant identity. With regards to self reported documentation practices, 16.4% of ED staff never questioned female patients about intimate partner violence, 83.6% asked when thought appropriate, and none asked routinely. None of the staff used a structured screening tool. 60% of ED staff documented their questioning but 92.7% did not use the DV-field for documentation. 58.2% of ED staff could not identify the DV field and 45.5% of respondents did not know how to interpret the DV field if positive.Conclusion: Our findings suggest that the current documentation tool (DV-field) is not being utilized. Furthermore, low rates of IPV documentation, and potentially questioning, in high risk patients indicates that there is need to improve current practises.